PERANCANGAN PERHIASAN BERBAHAN PEWTER - Budi Hartono (Corak : Jurnal Seni Kriya, 2018)
The use of tin as natural wealth in Indonesia for jewelry is not well known. White tin mixed with copper and antimony metal turns out to be a material that is visually appealing. In general, the materials used as jewelery in Yogyakarta, especially Kotagede are silver, brass and copper. White tin which is widely available in Indonesia can actually be used as an art product. Craftsmen prefer to use metals, such as silver, copper and brass. Generally, tin is used as a metal connecting material, whereas the white tin can be used as jewelry if mixed with antimony and copper in certain quantities. With a more affordable price, if it has become a well-worked art product, it will open up employment opportunities for the wider community. Direct observation and experimentation are the right methods in designing this product, through stages: a) Surveying, b) Synthesis, c) Design development, d) Evaluation will get comprehensive and near perfect data. Because in that way the community is no longer awkward to use quality pewter. The main reason pewter is attractive is that although the metal is not considered a precious metal, it is mixed with copper and antimony when it is almost the same color as silver. As a jewelry material, pewter has an attractive appearance. With a touch of contemporary design, it will add value to the material. Key Word : design, pewter, jewelry  Pemanfaatan timah putih sebagai kekayaan alam di Indonesia untuk bahan perhiasan belum cukup dikenal. Timah putih yang dicampur dengan logam tembaga dan antimonium ternyata bisa menjadi bahan perhiasan yang menarik secara visual. Secara umum, material yang dipakai sebagai bahan perhiasan di Yogyakarta, khususnya Kotagede adalah perak, kuningan, dan tembaga. Timah putih yang banyak terdapat di Indonesia sebenarnya bisa dimanfaatkan menjadi produk seni. Perajin lebih suka memanfaatkan logam, seperti perak, tembaga, dan kuningan. Umumnya, timah dijadikan bahan penyambung logam, padahal timah putih tersebut bisa dimanfaatkan menjadi bahan perhiasan apabila dicampur antimonium dan tembaga dalam takaran tertentu. Dengan harga yang lebih terjangkau, apabila sudah menjadi produk seni yang digarap dengan baik, akan membuka peluang kerja bagi masyarakat luas. Pengamatan langsung dan eksperimen merupakan metode yang tepat dalam perancangan produk ini, melalui tahapan: a) Survei, b) Sintesis, c) Pengembangan desain, d) Evaluasi akan diperoleh data yang komprehensif dan mendekati sempurna. Sebab dengan cara seperti itu masyarakat tidak canggung lagi untuk menggunakan pewter yang berkualitas. Alasan utama pewter menarik adalah jenis logam tersebut meskipun dianggap bukan jenis logam mulia, namun logam ini apabila dicampur dengan tembaga dan antimon akan memiliki warna yang hampir sama dengan perak. Sebagai material perhiasan, pewter memiliki penampilan yang menarik. Dengan sentuhan desain yang kekinian, akan menambah nilai material tersebut. Kata Kunci: perancangan, pewter, perhiasan